Sperm morphology assessment using strict criteria and male fertility under in-vivo conditions of conception - Eggert-Kruse, Waltraud; Schwarz, Heike; Rohr, Gerhard; Demirakça, Traute; Tilgen, Wolfgang; Runnebaum, Benno (Human reproduction, 1996)
The clinical significance of sperm morphology assessment according to very strict criteria was determined using semen samples of randomly chosen males from couples not submitted to assisted procreation techniques, with a median duration of infertility of 4 years (range 1-17; n = 89). The relationships of sperm morphological properties to the results of standard sperm analysis, including the differentiation of round cells in semen by monoclonal antibodies and semen cultures, the testing of sperm functional capacity in vitro with the standardized sperm-cervical mucus penetration test (SCMPT) and the subsequent pregnancy rate under in-vivo conditions of conception, were evaluated in a prospective study. The quick staining method (DiffQuick® stain) for sperm morphology proved to be practical and suitable for routine use* The percentage of normal forms according to strict criteria ranged from 1 to 36%, with a median of 12%. Morphological findings were not markedly related to the medical history, but significant relationships between standard parameters of sperm analysis, in particular the sperm count, the progressive motlity and standard sperm morphology, were found. The percentage of normal forms was not significantly associated with the microbial colonization of semen samples but was negatively related to high leukocyte rates. Semen samples with a higher percentage of normal spermatozoa (shown, for example, for >4, >7 or >14% normal) were significantly more frequent in cases of an adequate SCMPT. The subsequent pregnancy rate within an observation period of 12 months was 20.2%. The pregnancy rate under in-vivo conditions was significantly higher when semen samples had a better sperm morphology, with significant differences for thresholds at 4, 7 and 14% of strictly normal forms. Although sperm morphology is only one among a multiplicity of factors determining fertility, the results suggest that the evaluation of sperm morphology using strict criteria provides valuable information during basic infertility investigations.
Gesehen am 18.11.2024